The Digital Divide and Smartphone Reliance for Disadvantaged Students in Higher Education - Madhumita Banerjee (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The digital divide as it pertains to information inequality among disadvantaged student populations in higher education is a pertinent problem, and has been further exacerbated by the increase in online learning due to COVID-19. This study explores Technological Access challenges of students at a small public midwestern university in the US that serves a disproportionately higher number of underserved and underrepresented students. Survey data from 535 undergraduate students indicate that a critical subset (n=61) of the sample who were first generation, low income, and nonwhite had significantly lower levels of Technological Access with respect to access to devices and Internet access, when compared to the larger sample. Additionally, nearly half of the sample used smartphones to access courses online. Educational implications of smartphone dependence among disadvantaged students and the consequent digital divide are discussed. As technology induced online learning proliferates, addressing such gaps will be a step toward mitigating inequities plaguing higher education.